Forces of nature : a history of Florida land conservation - Henderson, Clay, 1955- (Gainesville : University Press of Florida, 2022)
"In this comprehensive history of land conservation in Florida, Clay Henderson celebrates the individuals and organizations who made the state a leader in state-funded conservation and land preservation"--
"The activists and victories that made Florida a leader in land preservation Despite Florida's important place at the beginning of the American conservation movement and its notable successes in the fight against environmental damage, the full story of land conservation in the state has not yet been told. In this comprehensive history, Clay Henderson celebrates the individuals and organizations who made the Sunshine State a leader in state-funded conservation and land preservation. Starting with early naturalists like William Bartram and John Muir who inspired the movement to create national parks and protect the country's wilderness, Forces of Nature describes the efforts of familiar heroes like Marjorie Stoneman Douglas and May Mann Jennings and introduces lesser-known champions like Frank Chapman, who helped convince Theodore Roosevelt to establish Pelican Island as the first national wildlife refuge in the United States. Henderson details how many of Florida's activists, artists, philanthropists, and politicians have worked to designate threatened land for use as parks, preserves, and other conservation areas. Drawing on historical sources, interviews, and his own long career in environmental law, Henderson recounts the many small victories over time that helped Florida create several units of the national park system, nearly thirty national wildlife refuges, and one of the best state park systems in the country. Forces of Nature will motivate readers to join in defending Florida's natural wonders. "--
Introduction: The Grandfather of the Future -- A Place Worth Saving -- The Naturalists -- Naval Live Oaks -- The Dawn of Conservation -- A National Cause -- Paradise Key -- Foreverglades -- The Rise of State Parks -- The Forests and the Trees -- Forces of Nature -- Biscayne Bay -- National Wildlife Refuges -- National Seashores -- From Boondoggle to Greenway -- Endangered Lands -- Preservation 2000 -- From Trails for Greenways -- The Business of Conservation -- The Conservation Amendment -- Florida Forever -- In Perpetuity -- A Mandate for Conservation -- Revenge of the Legislature -- Amendment 1 Begins to Pay Dividends -- The Future of Conservation.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 09, 2022).
eBooks on EBSCOhost
Keywords: Conservation of natural resources -- Florida -- History; Land use -- Florida -- History; Nature -- Effect of human beings on -- Florida; Nature conservation -- Florida; Conservation des ressources naturelles -- Floride -- Histoire; Utilisation du sol -- Floride -- Histoire; Êtres humains -- Influence sur la nature -- Floride; Nature -- Conservation -- Floride; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); NATURE / Regional; Conservation of natural resources; Land use; Nature conservation; Nature -- Effect of human beings on; Florida; Electronic books; History